2010
DOI: 10.1016/j.exer.2010.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptors in ocular surface disease

Abstract: The ability of the ocular surface to mount an immune response is in part attributed to a family of proteins called toll-like receptors (TLRs). The latter are evolutionary conserved receptors that recognize and respond to various microbes and endogenous ligands. In addition to their recognition function, TLR activation triggers a complex signal transduction cascade that induces the production of inflammatory cytokines and co-stimulatory molecules, thus initiating innate and adaptive immunity. Toll-like receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(71 citation statements)
references
References 92 publications
(110 reference statements)
1
70
0
Order By: Relevance
“…[17][18][19] At least 13 TLRs that recognize a limited but conserved set of ligands from viral, bacterial, protozoan, and helminth pathogens have now been identified in mice and humans. 20 -23 It was initially thought that TLRs are primarily expressed by antigen-presenting cells (APCs) such as macrophages and dendritic cells and that interactions between microbial ligands and TLRs in these cells would indirectly result in the activation of effector T cells (T eff cells).…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] At least 13 TLRs that recognize a limited but conserved set of ligands from viral, bacterial, protozoan, and helminth pathogens have now been identified in mice and humans. 20 -23 It was initially thought that TLRs are primarily expressed by antigen-presenting cells (APCs) such as macrophages and dendritic cells and that interactions between microbial ligands and TLRs in these cells would indirectly result in the activation of effector T cells (T eff cells).…”
Section: Discussionmentioning
confidence: 99%
“…The same applies to mononuclear cells. Several studies refer to expression of TLR members by ocular tissue (Pearlman et al 2010;Redfern and McDermott 2010). Although it is generally assumed that a high level of expression of a given TLR member indicates an efficient response to a PAMP, the study of expression is complicated by several factors: (1) it is not always clear whether nonexisting reports on certain TLR member expression means the virtual absence of a given TLR member from this tissue or organ, or a lack of relevant tools for analysis, or simply lacking information;…”
Section: Tlr Expression By Various Tissuesmentioning
confidence: 99%
“…Ueta et al [77] have shown polymorphisms in the TLR3 gene in patients with SJS (Stevens-Johnson syndrome) in a Japanese population and hypothesized that viral infection and/or drugs may trigger a disorder in the host innate immune response, leading to an abnormal inflammatory reaction of the mucosa, ocular surface and skin [8,13,19,77].…”
Section: Tlrs In Ocular Surface Immune Diseasesmentioning
confidence: 97%
“…TLRs may be classified based on their localization (intracellular or surface) or by their ligands, which are highly conserved structures expressed by pathogens (not expressed by host cells), enabling the innate immune system to distinguish between self and nonself. Table 1 summarizes the common ligands recognized by TLRs and evidence for the expression of TLRs on corneal and conjunctival epithelia [7,12,18,19]. TLR2 mainly forms heterodimers with either TLR1 or TLR6 to recognize several bacterial products.…”
Section: Tlr Expression At the Ocular Surfacementioning
confidence: 98%